The Relationship between Trauma Exposure and Serious Mental Health Conditions: A Focus on Africa and Low- and Middle-Income Countries - Stevenson, Anne Holm (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.